2014
DOI: 10.1136/jclinpath-2014-202248
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigation and antimicrobial susceptibility analysis of ureaplasma species andMycoplasmahominis in outpatients with genital manifestations

Abstract: Our study indicates that high positive rates of Ureaplasma species and M hominis were found in young outpatients with genital symptoms, and monitoring the local drug resistance is critical for prevention of the occurrence of resistant strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 16 publications
3
26
0
1
Order By: Relevance
“…Another Italian study, from De Francesco et al, obtained consistent results (10). Two Chinese analyses reported FQ resistance rates of Ͼ40% for Ureaplasma spp., while rates of resistance to macrolides and tetracyclines were Ͻ30% and Ͻ10%, respectively (8,9). In South Africa, Ureaplasma isolates had the following resistance rates: levofloxacin, 41%; moxifloxacin, 2%; ERY, 80%; TET, 73% (11).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another Italian study, from De Francesco et al, obtained consistent results (10). Two Chinese analyses reported FQ resistance rates of Ͼ40% for Ureaplasma spp., while rates of resistance to macrolides and tetracyclines were Ͻ30% and Ͻ10%, respectively (8,9). In South Africa, Ureaplasma isolates had the following resistance rates: levofloxacin, 41%; moxifloxacin, 2%; ERY, 80%; TET, 73% (11).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, in most countries the highest resistance rates have been recorded against FQs (8)(9)(10)(11)(12)(13)(14). This is undoubtedly due to their empirical overuse in the community (e.g., for urinary and respiratory tract infections), which contributes to the selection of amino acid substitutions in the QRDRs of DNA gyrase (GyrA and GyrB) and DNA topoisomerase IV (ParC and ParE) (20,26,27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two species that exist in humans, Ureaplasma parvum (UPA) contains serovars 1, 3, 6, and 14 and Ureaplasma urealyticum (UUR) contains serovars 2, 4, 5, 7, 8, 9, 10, 11, 12, and 13 . About 15%‐30% of healthy adult men may harbor Ureaplasma spp in their lower urogenital tract . During the past decade, many investigators reported that Ureaplasma spp.…”
Section: Introductionmentioning
confidence: 99%
“…clarithromycin, erythromycin, azithromycin and roxithromycin), but susceptible to 16-membered macrolides (josamycin and miocamycin) and lincomycin [6]. Increasing resistance to fluoroquinolones have been documented in several reports [8,9]. Therefore, rapid detection and susceptibility determination are important to start adequate treatment and to reduce the risk of complications.…”
Section: Introductionmentioning
confidence: 99%